1978
DOI: 10.1073/pnas.75.6.2708
|View full text |Cite
|
Sign up to set email alerts
|

Amino-terminal amino acid sequence of the major structural polypeptides of avian retroviruses: sequence homology between reticuloendotheliosis virus p30 and p30s of mammalian retroviruses.

Abstract: Communicated by Purnell W. Choppin, March 27, 1978 ABSTRACT The major structural polypeptides, p30 of reticuloendotheliosis virus (REV) (strain T) and p27 of avian sarcoma virus B77, have been compared with regard to amino acid composition, NH-terminal amino acid sequence, and immunological crossreaction. The amino acid composition of the two polypeptides is distinct, and a comparison of the first 30 NH2-terminal amino acids of REV p30 with that of the first 25 of B77 p27 yields only three homologous residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…This classification agrees well with the observations on tRNA primers and is also consistent with the results of immunological and nucleic acid hybridization comparisons of various retrovirus isolates (14). Studies of the latter type have suggested that the REV group of avian retroviruses is structurally related to type C viruses of mammalian origin and not to the major family of avian retroviruses, the ALSV group (1,2,18,25,27). For this reason we decided to determine whether REV conforms to any of the known patterns at the level of initiation of reverse transcription.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This classification agrees well with the observations on tRNA primers and is also consistent with the results of immunological and nucleic acid hybridization comparisons of various retrovirus isolates (14). Studies of the latter type have suggested that the REV group of avian retroviruses is structurally related to type C viruses of mammalian origin and not to the major family of avian retroviruses, the ALSV group (1,2,18,25,27). For this reason we decided to determine whether REV conforms to any of the known patterns at the level of initiation of reverse transcription.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, REVs are quite distinct serologically, show little or no nucleic acid homology with members of the ALSV group, and neither genetically complement nor interfere with members of the ALSV group (12,20,22,23,32,38,48). Several studies on the morphology, major structural polypeptides, and DNA polymerase of REVs, presumably focusing on associated helper virus, have suggested that they are more closely related to type C viruses of mammalian origin than to the ALSV group (1,2,18,25,27,51).…”
mentioning
confidence: 99%
“…In contrast, the REV group is horizontally transmitted as infectious agents among different species of birds (19,22). Several lines of evidence, including ultrastructural (21, 31), enzymatic (21), amino acid sequencing (10,18), and radioimmunological studies (2, 10), have established a mammalian origin for these oncogenic avian viruses. Thus, the present findings indicate that OMC-1 virus and DKV are in the evolutionary lineage that led to the generation of a group of oncogenic viruses capable of crossing the interclass barrier between mammals and birds.…”
mentioning
confidence: 99%
“…In this study, we determined the nucleotide sequence and chromosomal localization of a cloned human DNA segment carrying two putative exons homologous to the transforming gene (v-rel) of reticuloendotheliosis virus strain T (REV-T). The human c-rel sequences may provide a useful tool for studying the structure and function of this cellular oncogene in mammals.REV-T is a replication-defective (11) type C retrovirus (3,12,25,36) that induces acute leukemia in young chickens and turkeys (32). It is the only known acutely transforming member (9, 10) of a retroviral family that includes spleen necrosis virus, chick syncytial virus, duck infectious anemia virus, and the REV-T helper reticuloendotheliosisassociated virus (REV-A) (11,14).…”
mentioning
confidence: 99%
“…REV-T is a replication-defective (11) type C retrovirus (3,12,25,36) that induces acute leukemia in young chickens and turkeys (32). It is the only known acutely transforming member (9, 10) of a retroviral family that includes spleen necrosis virus, chick syncytial virus, duck infectious anemia virus, and the REV-T helper reticuloendotheliosisassociated virus (REV-A) (11,14).…”
mentioning
confidence: 99%